Гурван Баттөмөрийн учрыг нэхэн тодруулсан минь - Мөнхбаяр, Халтар (Historia Mongolarum, 2009)
1950-иад он хүртэлх хугацаанд Монголын албан баримтад хүний овог буюу эцгийн нэрийг бичдэггүй байснаас түүх бичлэгт адил нэртэй хүмүүсийг хооронд нь андуурах явдал гарах болсон. Үүний жишээ бол Баттөмөр хэмээх адил нэртнүүд юм. Тиймээс энэхүү судалгаагаар тэдгээр Баттөмөрийн учир ялгааг олж, хэн хэн болохыг тогтоолоо. In historical research, people who have same named had been misidentified because of one’s surname wasn’t written in official document or Mongolia until 1950. Example or these is people who named Ballumur. Therefore, this research was conducted to find out differences between those Battumurs and it was found out that there were three Battumurs: Battumur Gongor of full fower representative or the Mongolian People’s Revolutionary Party; Battumur Tsend of minister of the Mongolian People’s Culture, and Education; and Battumur Jigmed of vice minister of the Mongolian Trade and Transportation.